McGraw Hill's Dictionary of American Idioms and Phrasal Verbs : The most practical reference to the idiomatic and verbal expressions of contemporary American English - Spears, Richard A. (McGraw Hill, 2005)
xvii, 1080 p. : il.; 27 cm.